2000
DOI: 10.1073/pnas.150130197
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-coupled repair in yeast is independent from ubiquitylation of RNA pol II: Implications for Cockayne's syndrome

Abstract: Cockayne's syndrome cells lack transcription-coupled nucleotide excision repair (TCR) and ubiquitylation of RNA polymerase II large subunit (RNA pol II LS), suggesting that ubiquitylation of RNA pol II LS may be necessary for TCR in eukaryotes. Rsp5 is the sole yeast ubiquitin-protein ligase that ubiquitylates RNA pol II LS in cells exposed to DNA-damaging agents. In yeast lacking functional Rsp5, there is no ubiquitylation of RNA pol II LS. We show here that removal, repression, or over-expression of Rsp5 has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Second, a DDB1 sequence homolog has not been identified. Finally, Rsp5, the only E3 which ubiquitinates Rpb1 in S. cerevisiae, is also dispensable for TCR (31). In the course of UV survival assays, we noticed that the UV survival of the ⌬ddb1 ⌬uvde and ⌬rhp26 ⌬uvde mutants were not similar (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Second, a DDB1 sequence homolog has not been identified. Finally, Rsp5, the only E3 which ubiquitinates Rpb1 in S. cerevisiae, is also dispensable for TCR (31). In the course of UV survival assays, we noticed that the UV survival of the ⌬ddb1 ⌬uvde and ⌬rhp26 ⌬uvde mutants were not similar (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Important in this connection, Pol II becomes ubiquitylated and degraded in response to DNA damage (Beaudenon et al, 1999;Bregman et al, 1996;Luo et al, 2001;Ratner et al, 1998), which raises the possibility that it is removed from lesion sites so that rapid repair can take place. However, enabling TCR is unlikely to be the function of Pol II proteolysis (Lommel et al, 2000;Woudstra et al, 2002). Rather, a new study suggests that ubiquitylation and Pol II degradation in response to DNA damage constitutes an alternative to DNA repair -a last resort (Woudstra et al, 2002).…”
Section: Proteolysis Of Pol II In Response To Dna Damagementioning
confidence: 99%
“…More recent data indicate that degradation of the Pol II LS is not an absolute requisite for repair of cisplatin adducts, at least in model systems using cellular extracts from human cells (Tremeau-Bravard et al, 2004;Sarker et al, 2005;Lainé and Egly, 2006a). Furthermore, yeast mutants lacking ubiquitin ligase, and thus unable to ubiquitylate the stalled Pol II LS, are still TCR proficient (Lommel et al, 2000). Furthermore, it has been shown that proteolysis of the Pol II LS can occur independently of the TCR process as treatment with alpha-amanitin or nucleotide starvation is accompanied by ubiquitylation and proteolysis of the polymerase (Lee et al, 2002;Yang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%